THE ABUNDANCE AND COMPOSITION OF FISH SPECIES BASED ON FISHING GEAR IN THE WATERS OF LAKE LINDU, CENTRAL SULAWESI PROVINCE - Zainal, Syech; Djirimu, Muchlis; Sabran, Moh.; Firdaus, Firdaus (e-JIP BIOL, 2017)
This research was conducted in the waters of Lake Lindu Central Sulawesi Province in January to February with the aim of research is to describe the abundance and composition of fish species based on fishing gear in the waters of lake lindu, central sulawesi province. The method used is survey by taking samples using gill net fishing gear, fishing line, and stratified sampling method. Sampling based on time of arrest that is morning and afternoon at four station. The results of the study found 10 species, among them Oreochromis mosambicus, Oreochromis niloticus, Anabas testudineus, Cyprinus carpio, Clarias batrachus, Puntius gonionotus, Channa striata, Osphronemus gouramy, Anguilla marmorata and Anguilla bicolor. The composition of fish species based on the means of catching in a row is by catching gill net (Gill net) by 50%, 38% bubu and 12% fishing line.Â Keyword: The composition of fish species, types of fishing gear, waters of Lake Lindu.